Pengaruh Larutan Madu terhadap Tekanan Darah Lanjut Usia Hipertensi - Siti Aulia Musyayyadah; Joyeti Darni; Fathimah fathimah (Universitas Islam Negeri Walisongo Semarang, 2019)
This study aimed to determine the effect of honey solution intervention on systolic blood pressure and elderly diastole in the Aisyiyah Nursing Home Surakarta. Method of this research using Quasi-experimental approach with a pre-posttest control group design with 24 respondents selected by purposive sampling and divided into 4 groups there are O1 (70 gr honey), O2 (35 gr honey), K- (control with hypertension) and K+ (control with normotensive). Measurement of blood pressure using an Omron Sphygmomanometer. Paired Sample T-test was used to determine the effect of blood pressure before and after the intervention. The One Way ANOVA test was used to see differences in the average blood pressure data before the intervention. The results showed that there was an effect of honey solution on systolic blood pressure before and after intervention with p = 0,000 (p 0,05), as well as diastolic blood pressure in the statistical test, showed that there was an effect of honey solution on blood pressure diastole before and after intervention with p = 0,001 (p 0,05). So, there was a significant effect on the intervention of honey solution with 35 and 70 gr honey dose on systolic and diastolic blood pressure in the elderly.